SOME ISSUES IN THE QUALIFICATION OF ABUSE OF POWER OR CAREER AUTHORITY - Ikramov Akmal Nuritdinovich (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
The article emphasizes that today а special place in the system of crimes against the management order is the social danger of the crime of abuse of authority or career, which as a result of this crime is considered socially dangerous with a large or serious loss of rights of certain citizens or interests guarded by law or the interests of the state or society. The social danger of this crime in the form of organized crime and corruption is further increased by the fact that it becomes extremely dangerous, the state becomes dangerous by the fact that it causes the consequences of the crisis of society also cause the characteristics of risk.